Perencanaan pembelajaran Berbasis Permainan Tradisional sebagai Afirmasi Literasi Budaya di SD - Anis Nurjannah; Seni Apriliya; Aji Mustajin (Universitas Pendidikan Indonesia (UPI), 2020)
AbstractThis paper describes the game-based learning as an affirmation of cultural literacy in elementary school. The low literacy rate of the Indonesian nation, demanding the solution of various lines. The role of academics, including the drafting of various literacy programs as well as product quality. Based on observations, learners (children) in elementary school tended to lack of concentration for long periods during the following study; on the other hand the children can follow and enjoy the game in a relatively long period of time. The game is an activity drives all the senses and sensory motor fun or exciting (Sutton-Smith, 1997 in scarlet, et. Al, 2005; Bergen, 2009; Hynoven, 2011); As for the traditional games refer to games with a certain cultural background. Affirmations literacy is a reinforcement of all forms of literacy from the conceptual level to procedural, by individuals, community groups, or governments to improve the literacy skills (Apriliya, 2016). Cultural literacy is the knowledge and understanding of how a country, a religion, an ethnic group or a tribe, religion, symbols, celebrations, and traditional communication means (Nasution, 2013). At the time following the game, children are required to understand and interact culturally in the context of the game, not just having fun, children are expected to have the cultural literacy of the game is done. Approach Educational Design Research (Eder) can be used to develop devices and game-based learning model as an affirmation of literacy in elementary school. Learning plan based on the approach Eder produce learning tools such as Learning Implementation Plan (RPP), teaching materials in the form of Student Worksheet, and instrument ratings.AbstrakTulisan ini memaparkan pembelajaran berbasis permainan sebagai afirmasi literasi budaya di SD. Rendahnya angka literasi bangsa Indonesia, menuntut solusi dari berbagai lini.Peran akademisi, di antaranya dengan melahirkan berbagai program maupun produk literasi yang bermutu.Berdasarkan hasil observasi, peserta didik (anak-anak) di SD cenderung kurang konsentrasi dalam jangka waktu lama pada saat mengikuti pembelajaran; di sisi lain anak-anak dapat mengikuti dan menikmati permainan dalam jangka waktu yang relatif lama. Permainan merupakan kegiatan menggerakkan seluruh pancaindera dan sensori motorik yang menyenangkan atau menggembirakan (Sutton-Smith, 1997 dalam scarlet, et. al, 2005; Bergen, 2009; Hynoven, 2011); adapun permainan tradisional merujuk pada permainan dengan latar budaya tertentu. Afirmasi literasi merupakan segala bentuk penguatan literasi mulai dari tataran konseptual sampai prosedural, yang dilakukan individu, kelompok masyarakat, atau pemerintah untuk meningkatkan kemampuan literasi (Apriliya, 2016). Literasi budaya merupakan pengetahuan dan pemahaman tentang bagaimana suatu negara, agama, sebuah kelompok etnis atau suatu suku, keyakinan, simbol, perayaan, dan cara komunikasi tradisional (Nasution, 2013). Pada saat mengikuti permainan, anak-anak dituntut untuk memahami dan berinteraksi sesuai budaya dalam konteks permainan tersebut, tidak hanya sekadar bersenang-senang, anak-anak diharapkan untuk memiliki literasi budaya dari permainan yang dilakukan.Pendekatan Educational Design Research (EdeR) dapat digunakan untuk mengembangkan perangkat dan model pembelajaran berbasis permainan sebagai afirmasi literasi di SD. Perencanaan pembelajaran berdasar pada pendekatan EdeR menghasilkan perangkat pembelajaran berupa Rencana Pelaksanaan Pembelajaran (RPP), bahan ajar berupa Lembar Kerja Siswa (LKS), dan instrumen penilaian.